(untitled) (Bangladesh Journal of Botany, 2023)
Spraying of chilli crop with fenpropathrin @ 75 and 150 g a.i./ ha led to the initial residues ranging from 0.12 to 0.14 and 0.19 to 0.22 mg/kg, respectively. Fenpropathrin residues in chilli dissipated below the limit of quantification after 3 and 5 days at low and high doses. The half-life of fenpropathrin in chilli was calculated to be 2.41 and 1.92 days. Residues of fenpropathrin on chilli collected 0 day after spray was below MRL following application @ 75 g a.i./ ha. Among various household processing methods, KMnO4 solution reduces 72.50 per cent residue washing, boiling, dipping in sodium bicarbonate solution, salt solution and acetic acid solution, respectively after 0 (2 hrs after spray) day of fenpropathrin @ 75 g a.i./ ha after third spraying in chilli. Bangladesh J. Bot. 52(3): 715-722, 2023 (September)